The Role of Accounting in Financial Management of Fund Allocation : JEL Classification: H61; H72; M41; O18; R58 - Wal Ming Walda; Ilham Z. Salle; Jumriani Jumriani (Maroon Journal De Management, 2026)
This study aims to examine the Role of Accounting in the Financial Management of Village Fund Allocation in Tiwu Riwung, Mbeliling District. This study uses a qualitative method with in-depth interviews with related parties in Tiwu Riwung Village and direct observation of the accounting system. The results of the study indicate that the Village Fund Allocation Financial Accounting System used is by using the Microsoft Excel program in the form of a General Cash Book and a Subsidiary Cash Book for Receipts and a Subsidiary Cash Book for Expenditures. Meanwhile, the Financial Management of Village Fund Allocation in Tiwu Riwung Village is quite good and the realization is because it has been arranged according to the Budget Plan (RAB). Where one of the sources of Village Income is obtained from the Village Fund Allocation which is used for fixed income and allowances for village officials, office operations, consumables, printing and procurement, food and drinks during meetings, BPD allowances, village administration and information development systems.